The adsorption of lead(II), iron(III) and cadmium(II) ions to S.leibleinii and R.arrhizus in air-mixed coloumn - Özer, Ayla; Özer, Dursun; Ekiz, H. Ibrahim; Kutsal, Tülin; Ça?lar, Arif (My University, 1996)
The adsorption of lead(II), iron(III) and cadmium(II) ions to S.ieibleinii and R.arrhizus was investigated in air-mixed coloumn. Freundlich and Langmuir adsorption isotherms were developed at optimum initial pH values obtained for each microorganism and at 30°C. Experimental results show that adsorption capacities and yields of iron(III) to both microorganism were better than those of cadmium(II) and lead(II).
Kurşun(II), demir(III) ve kadmiyum(II) i?yonlarinin hava ile Kariştirmali kolonda S.leibleinii ve R.arrhizus'a adsorbsiyonu
Keywords: Air-Mixed Coloumn; Heavy Metal Adsorption; The Adsorption Isotherms